“TAKE ME OUT INDONESIA” : REALITA PENCARIAN JODOH PEREMPUAN MELALUI MEDIA - Shafra Shafra (Marwah: Jurnal Perempuan, Agama dan Jender, 2011)
Reality show, Take Me Out Indonesia is a TV program in Indonesia that gives a new nuance to women so as not to depend on parents or others in determining a soulmate. The phenomenon of mate searching through the media illustrates that if women are just waiting for a soul mate to come is no longer fit with the times. Women have the right to itself to find, select, and apecify partner. Thus, there has been a shift in the understanding and attitudes about the meaning of partner search. Women are no longer ashamed to declare the man who wants to become a couple. He has had an open attitude, thingking and choices about men, dating and marriage she wants. Indeed, in the community there is controversy about the show mate search, as mentioned, because some people consider it incompatible with the norms and ethics policies, especially the norms of religion (Islam) that is still strongly held by most of the people of Indonesia. Islam indeed recognizes individual rights of women to find his life partner, butthere are certain ethics that must be considere.